Oral pilocarpine for the treatment of dry eye in patients with Sjögren’s syndrome - Felberg,Sergio (2022)
ABSTRACT Purpose: To evaluate the efficacy of oral pilocarpine (20 mg daily) for the treatment of dry eye in patients with Sjogren’s Syndrome. The frequency of side effects reported during the treatment was also investigated. Methods: In this placebo-controlled crossover study, 32 patients with Sjögren’s syndrome were enrolled to receive either oral pilocarpine or placebo for 10 weeks. Following a 2-week washout period, the treatment was inverted for each patient for the same duration. Assessments included the quality of life National Eye Institute Visual Function Questionnaire-25 (NEI-VFQ-25), dry eye specific questionnaire Ocular Surface Disease Index, non-invasive breakup time, invasive breakup time with fluorescein, corneal and conjunctival staining patterns with the use of fluorescein and rose bengal staining, Schirmer’s test, and tear ferning test. Results: According to the NEI-VFQ-25, there was statistically significant improvement in the quality of life following oral pilocarpine. Similar results were observed for ocular discomfort, as determined by the Ocular Surface Disease Index. All clinical tests showed favorable and statistically significant results following the use of oral pilocarpine. Regarding the analysis of tear samples, there was an improvement in the quality of tear film. This was evidenced by the modification of the patterns observed in the tear ferning test. Side effects were reported by 96.8% and 56.2% of the patients who received pilocarpine and placebo, respectively. Sweating was the most frequently reported side effect (67.74% versus 11.11%, respectively). Conclusions: Although the treatment was associated with a high frequency of side effects, oral pilocarpine (20 mg daily) was able to relieve discomfort related to dry eyes in patients with Sjögren’s syndrome and induce favorable structural changes in the tear film.